Mice with a deficiency in Peroxisomal Membrane Protein 4 (PXMP4) display mild changes in hepatic lipid metabolism - Blankestijn, Maaike; Bloks, Vincent W.; Struik, Dicky; Huijkman, Nicolette; Kloosterhuis, Niels; Wolters, Justina C.; Wanders, Ronald J. A.; Vaz, Frédéric M.; Islinger, Markus; Kuipers, Folkert; van de Sluis, Bart; Groen, Albert K.; et al. (Scientific reports, 2022)
Peroxisomes play an important role in the metabolism of a variety of biomolecules, including lipids and bile acids. Peroxisomal Membrane Protein 4 (PXMP4) is a ubiquitously expressed peroxisomal membrane protein that is transcriptionally regulated by peroxisome proliferator-activated receptor α (PPARα), but its function is still unknown. To investigate the physiological function of PXMP4, we generated a Pxmp4 knockout (Pxmp4−/−) mouse model using CRISPR/Cas9-mediated gene editing. Peroxisome function was studied under standard chow-fed conditions and after stimulation of peroxisomal activity using the PPARα ligand fenofibrate or by using phytol, a metabolite of chlorophyll that undergoes peroxisomal oxidation. Pxmp4−/− mice were viable, fertile, and displayed no changes in peroxisome numbers or morphology under standard conditions. Also, no differences were observed in the plasma levels of products from major peroxisomal pathways, including very long-chain fatty acids (VLCFAs), bile acids (BAs), and BA intermediates di- and trihydroxycholestanoic acid. Although elevated levels of the phytol metabolites phytanic and pristanic acid in Pxmp4−/− mice pointed towards an impairment in peroxisomal α-oxidation capacity, treatment of Pxmp4−/− mice with a phytol-enriched diet did not further increase phytanic/pristanic acid levels. Finally, lipidomic analysis revealed that loss of Pxmp4 decreased hepatic levels of the alkyldiacylglycerol class of neutral ether lipids, particularly those containing polyunsaturated fatty acids. Together, our data show that while PXMP4 is not critical for overall peroxisome function under the conditions tested, it may have a role in the metabolism of (ether)lipids.